2015
DOI: 10.12691/jfnr-3-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Health Benefits of Brown Algae (<i>Sargassum muticum</i>) in Volunteers

Abstract: A randomized clinical trial enrolling healthy volunteers was carried out to evaluate the effects of S. muticum supplementation. An experiment was conducted to investigate whether intake of S. muticum could exert beneficial effects on human health. Volunteers were asked to consume dried encapsulated S. muticum 4.8 grams daily for 4 weeks. Analysis was made on several parameters including blood lipid profile, stress hormone level, fatigue status, liver functions, and lymphocyte subpopulation level, before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, a British company, Haeckles, is exploring the production of a nutritional drink based on seaweed found on the Kent coast including S. muticum (Bridges, Haeckles private communication 2015), and S. muticum has been suggested as a general nutraceutical for the prevention and treatment of cancer due to the presence of antioxidants, antimicrobial and antitumor compounds within it (Namvar et al 2013). A study using S. muticum as a dietary supplement found that it produced a 14 % reduction in blood low-density lipoprotein (believed to be a major contributor to atherosclerosis) and an increase in natural killer NK lymphocytes (Park et al 2015). However, considerable care should be taken in the use of seaweeds for food since brown macroalgae, including S. muticum, contain much higher levels of absorbed heavy metals than terrestrial plants (Carro et al 2015;Lodeiro et al 2004;Ungureanu et al 2015).…”
Section: Foodmentioning
confidence: 99%
“…However, a British company, Haeckles, is exploring the production of a nutritional drink based on seaweed found on the Kent coast including S. muticum (Bridges, Haeckles private communication 2015), and S. muticum has been suggested as a general nutraceutical for the prevention and treatment of cancer due to the presence of antioxidants, antimicrobial and antitumor compounds within it (Namvar et al 2013). A study using S. muticum as a dietary supplement found that it produced a 14 % reduction in blood low-density lipoprotein (believed to be a major contributor to atherosclerosis) and an increase in natural killer NK lymphocytes (Park et al 2015). However, considerable care should be taken in the use of seaweeds for food since brown macroalgae, including S. muticum, contain much higher levels of absorbed heavy metals than terrestrial plants (Carro et al 2015;Lodeiro et al 2004;Ungureanu et al 2015).…”
Section: Foodmentioning
confidence: 99%
“…In the last decade, many researchers paid attention to Sargassum sp. from nutritional point of view [6]- [11]. Certain species as S. fusiforme, S. horneri, S. pallidum, and S. thunbergii used in herbal medicine [12].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive body of work in vitro has been published to evaluate this and other seaweed-derived carotenoids, with some described in Section 5 [ 139 , 172 , 173 ]. There are a few additional studies with whole seaweed and mixed extracts, which also provide valuable information on the effects of dietary intake of seaweed [ 174 , 175 ]. During uptake, fucoxanthin is metabolized to fucoxanthinol and amarouciaxanthin A, which were found in the adipose tissue, kidney, heart, lung, and spleen of mice [ 176 , 177 ].…”
Section: Main Marine Organisms Containing Carotenoidsmentioning
confidence: 99%